A Fluorogenic Probe with Aggregation‐Induced Emission Characteristics for Carboxylesterase Assay through Formation of Supramolecular Microfibers. Issue 3 (8th January 2014) - Wang, Xiaojing; Liu, Huan; Li, Jingwen; Ding, Kaiguo; Lv, Zhonglin; Yang, Yonggang; Chen, Hong; Li, Xinming
Abstract Herein, we report a novel fluorescent "light‐up" probe useful for carboxylesterase assay that is based on a tetraphenylethylene derivative containing carboxylic ester groups. The specific cleavage of the carboxylic ester bonds by carboxylesterase results in the generation of a relatively hydrophobic moiety that self‐assembles into supramolecular microfibers, thus giving rise to "turn‐on" fluorescent signals. A high sensitivity towards carboxylesterase was achieved with a detection limit as low as 29 pM, which is much lower than the corresponding assays based on other fluorescent approaches.